The Phonological Interference of Acehnese in Pronouncing Indonesian Language - Suhery, Dedy; Idami, Zahratul; Wati, Shafrida (JOLLT Journal of Languages and Language Teaching, 2024)
Linguistic issues such as interference and integration frequently arise in multilingual environment, which frequently result in barriers to second language production. This study examines at how language interaction between Acehnese and Indonesian has affected the Indonesian language in Langsa, with a particular emphasis on consonant variations and interference. The objective of this study was to investigate the influence of phonological interference on Acehnese speakers when speaking the Indonesian language, with a specific focus on observing variations in consonant sounds using auditory means.Â The study conducted a detailed examination of common variances in Indonesian pronunciation among Acehnese speakers.Â This qualitative research was carried out in Langsa, Aceh Province, involvingÂ 40 individuals who are native speakers of Acehnese. The participants consisted of 20 males and 20 females, encompassing a range of ages.Â The collected data was evaluated using the PRAAT software.Â The findings revealed that there was interference in pronunciation, particularly in the form of devoicing, which is the absence of vowel resonance. This was observed in the words "[ap. di]" and "[Ê¤a.wap]."Â This interference leads to a significant level of devoicing, reaching 90% and 100% respectively.Â Furthermore, the study revealed phonological interference in words such as "[thÉ™.linga]", "[tÉ™.thap]", and "[a.hat]", with speakers demonstrating devoicing rates of 40%, 40%, and 100% respectively.Â The findings showed the complex nature of phonological interference in the pronunciation of the Indonesian language by Acehnese speakers.Â These findings served as a foundation for the development of more effective strategies for acquiring a second language, particularly in diglossic environments like Indonesia.